(untitled) (Pedagogy of Higher and Secondary Education, 2007)
In the article the author defines teacher’s main professional qualities in the context of the subject approach, research’s the forming of professional valuable orientations, defines motives of the choice of the profession, reveals student’s professional tendencies and skiles of setting their professional aims.